Interaction of emigration and immigration with foreign direct investment, international trade and remittances - Antonio Mihi-Ramirez; Janusz Sobierajc; Yolanda Garcia-Rodriguez (Kiel Institute for the World Economy (IfW), 2019)
This paper studies the international mobility of capital and labour. Using a Mixed Linear Model (MMA) the authors analyse the interaction of emigration and immigration with foreign direct investment, exports and imports, and international remittances. The sample comprises 112 countries with which Spain has closely interconnected migratory, commercial and investment exchanges, and they focus both on the period prior to the great recession, 1998-2007, and on the subsequent period, 2008-2016. The results show that a greater number of immigrants in Spain boost foreign direct investment (FDI), remittances sent and received and Spanish imports andexports to the immigrants' countries of origin. In contrast to what was often stated in the classicalapproaches, this relationship is maintained in the long term and also has effects on emigration. Thus, an inverse relationship of emigration from Spain with the FDI and remittances sent is confirmed. With the economic downturn, the FDI declines and the number of migrants from Spainand remittances received began to increase. In a sense, FDI and migration could also be seen as a kind of risk aversion strategy. In fact, when looking at the behaviour of these variables together across a wide sample of countries and years, it is observed that immigration and emigration act as two sides of the same coin. The results lead the authors to recommend those strategies and policiesthat serve to take advantage of and promote the interaction of mobility factors, since it allows diversifying risks of companies and workers and finding new commercial and investment opportunities.
https://doi.org/10.7910/DVN/WFB8CW
Keywords: F10; F21; F22; F24; 330; emigration; immigration; foreign direct investment; exports; imports; remittances; linear mixed model